Ultra-High-vacuum Experimental Equipment to Characterize Shape Memory Alloys for Space Applications. (2015) - López-Ferreño, I.; Urrutia, U.; Lorenzo, P.; Collado, M.; Rivera, C.; Escudero, N.; Breczewski, T.; Nó, M.L.; Juan, J. San
Abstract: An experimental ultra-high-vacuum facility capable of measuring the deformation during thermal cycles under load at different temperatures has been designed and developed to characterize the shape memory effect in the environmental and working conditions imposed by the aerospace industry. In the current work the description of the equipment working at 2x10 -8 mbar between -180 °C up to 200 °C is presented, as well as several sets of measurements of thermally induced transformation under load in SMAs.